2000
DOI: 10.1128/mcb.20.12.4224-4237.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interference Footprinting Analysis of Telomerase Elongation Complexes

Abstract: Telomerase is a reverse transcriptase that adds single-stranded telomeric repeats to the ends of linear eukaryotic chromosomes. It consists of an RNA molecule including a template sequence, a protein subunit containing reverse transcriptase motifs, and auxiliary proteins. We have carried out an interference footprinting analysis of the Tetrahymena telomerase elongation complexes. In this study, single-stranded oligonucleotide primers containing telomeric sequences were modified with base-specific chemical reag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…2 B-E). This apparent uncoupling of the register of DNA-TERT interaction from the register of DNA-template interaction is consistent with results from our previous DNA footprinting and kinetic assays (10,18,19).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…2 B-E). This apparent uncoupling of the register of DNA-TERT interaction from the register of DNA-template interaction is consistent with results from our previous DNA footprinting and kinetic assays (10,18,19).…”
Section: Discussionsupporting
confidence: 92%
“…This position was previously shown to be involved in primer interaction with telomerase (10,13). A complex of reconstituted core enzyme (tTERT and tTER) with primer was irradiated with a long-wavelength UV light (Ͼ295 nm), thereby favoring crosslinks of the IdU with aromatic amino acids in close proximity.…”
Section: Mapping Of Dna Crosslinking Sites In Catalytically Active Tementioning
confidence: 99%
See 1 more Smart Citation
“…8). The specificity of the nascent product interaction would be reflected in the template and/or product sequence requirements described above and possibly by the inhibition of primer use upon dimethyl sulfate modification of terminal guanosines at the N-7 position, which is not predicted to affect base pairing with the template (25). If nascent product interaction can persist in the absence of a template hybrid, the proposed telomerase nascent product binding site would more closely resemble that of an RNA polymerase than a viral RT, which interacts with product in the context of the minor groove of a template-product hybrid (26).…”
Section: Figmentioning
confidence: 99%
“…Using for these assays oligo primers aligned at different positions along the template, we identified strong interactions of both types of enzyme with six to seven nucleotides at the 3′-termini of the primers. [16][17][18] Subsequently, we used ultraviolet light (UV) cross-linking techniques and site-directed mutagenesis to map amino acids in TERT that interact with DNA primers in complexes generated with the reconstituted core enzyme. These studies revealed a major interaction between the amino acid tryptophan 187 (W187) in the TEN domain of TERT and primer nucleotides aligned at the beginning of the RNA template region.…”
Section: Introductionmentioning
confidence: 99%